DETERMINAN AUDITOR SWITCHING PADA PERUSAHAAN FINANCE YANG TERDAFTAR DI BEI - Muhammad Fauzi; Amir Hasan; Vera Oktari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
This study aims to examine the factors that determine the change of auditors in finance companies. Companiy growth, audit delay, firm size, managerial ownership, change in management, financial distress, KAP size, and audit opinion used to determine auditor switching. The sample used in this study consisted of 11 samples of finance companies listed on the Indonesian Stock Exchange during 2013-2017. The sample in this study used purposive sampling method. Data analysis method uses logistic regression analysis using SPSS version 23.0. The result shows company's growth, audit delay, company size, management financial distress have effect on switching Auditors while audit opinion,KAP size and managerial ownership has no effect on auditor switching.